2021
DOI: 10.1007/s00423-021-02129-5
|View full text |Cite
|
Sign up to set email alerts
|

Composite phaeochromocytomas—a systematic review of published literature

Abstract: Introduction Composite phaeochromocytoma is a tumour containing a separate tumour of neuronal origin in addition to a chromaffin cell tumour. This study reports on two cases from a single centre’s records and presents a systematic literature review of composite phaeochromocytomas. Methods In addition to describing 2 case reports, a systematic search of the Medline database from inception up to April 2020 was done for human case reports on composite phaeoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 74 publications
3
37
0
Order By: Relevance
“…Currently, it is suggested that all patients diagnosed with CP require long-term follow-up, since the clinical course is highly unpredictable. In general, for composite PCC/PGL-GN, the prognosis has been promising based on previous publications, with extreme rare metastasis or death (Table S2) (1,2,8,(23)(24)(25)32,(35)(36)(37)(38)(39)(40)(41)(42)(43). However, careful follow-up is still recommended and predictors for prognosis are waiting to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is suggested that all patients diagnosed with CP require long-term follow-up, since the clinical course is highly unpredictable. In general, for composite PCC/PGL-GN, the prognosis has been promising based on previous publications, with extreme rare metastasis or death (Table S2) (1,2,8,(23)(24)(25)32,(35)(36)(37)(38)(39)(40)(41)(42)(43). However, careful follow-up is still recommended and predictors for prognosis are waiting to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Composite pheochromocytoma/paraganglioma (CP) is a rare neoplasm consisting of pheochromocytoma (PCC) or paraganglioma (PGL) combined with developmentally related neurogenic tumor (1). Its neurogenic component is various, including ganglioneuroma (GN), neuroblastoma, ganglioneuroblastoma, etc (1,2). Currently, little is known about its pathogenesis and relationship with its pure tumor counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Ganglioneuroma is a benign tumor arising from the neural crest, Schwannien stroma, and connective tissue of the sympathetic channel. It mainly occurs in the posterior mediastinum or retroperitoneum, but also in the adrenal glands and the neck [ 1 , 2 ]. AGN is rare, representing 21% of all GNs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the aggressive spectrum, there is neuroblastoma, while at the other end exhibiting generally considered benign features there is ganglioneuroma (3). Adrenal medulla is also the origin of pheochromocytomas with different grades of differentiation and associated malignant potential and also composite pheochromocytoma, a distinct rare entity (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Ganglioneuroma, a benign tumor of neuroblastic type, originates from the autonomous sympathetic nervous system, either central or peripheral; thus, the sites can be anywhere in relationship to the presence of autonomic ganglia such as the adrenals, retroperitoneum, mediastinum/thorax, and cervical area (4,5). Ganglioneuroma is considered to be a tumor with the least aggressive profile among all neuroblastic tumors since it exclusively has mature cells; it is also the rarest tumor of this category (6).…”
Section: Introductionmentioning
confidence: 99%